Development of a mechatronic weft selector to enhance patterning capacity in Rapier looms - Aiead Ibne Fahim; Md. Mohaddesh Hosen; Md. Abdullah Al. Mamun; Shah Alimuzzaman Belal (PLoS ONE, 2025)
Rapier weaving machines are widely used in the weaving industry; however, the design of the current weft selectors limits their capability to produce fabrics incorporating a large variety of weft yarns. Nevertheless, increasing the number of wefts with the existing selectors can impose challenges for the rapier in the efficient gripping of the weft. This study presents the design and development of a novel mechatronic weft selection system aimed at significantly enhancing the patterning capabilities of rapier looms. The proposed system features a circular arrangement of up to 20 weft yarn feeders and a single programmable selector module capable of handling the weft yarns. The selector integrates stepper motors, servo motors, solenoid valves, and an Arduino Mega-based control unit to execute user-defined weft patterns with high precision. The device was successfully operated at 9 picks per minute (PPM) across various yarn types, including polyester, viscose, and elastomeric yarns. A total of 11 different yarns were tested, each subjected to 5 trials using 20 feeders, resulting in the insertion of 1100 wefts. The system achieved a 100% selection and insertion success rate after the trials. The system also maintains a constant yarn-to-rapier angle, mitigating pick errors. The developed system offers a solution for expanding weft selection in rapier looms, enabling more intricate fabric designs and increased product versatility. To the best of our knowledge, this type of design has not been tried before in weft selection.